SURVEY FAKTOR-FAKTOR YANG MENDUKUNG TERJADINYA ISPA PADA LANSIA DI POLIKLINIK DALAM RSUD ENDE 2013 - MARTINUS RUKU (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
The process of aging is a process that converts healthy adults become brittle, along with declining reserves, almost all physiological systems and accompanied by increased susceptibility to disease and death. The purpose of the study was to determine the factors that contribute to respiratory disease in the elderly.This type of research is penelititan descriptive survey research design, the population of 78 people with a sample of 30 people. Sampling with accidental sampling technique, using ordinal scales, data collection devices with multiple choice questionnaire and the data processed manually. Elderly research results that are most affected by respiratory diseases is 58.3% with male sex work ARD elderly who suffer most are farmers (41.65%). Respondents' awareness of respiratory disease was (58.3%) had good knowledge, (41.7%) had less knowledge. The state of home environment/jobs (75%), dusty environment. State of the lighting in the house is (91.7%) of light. How to process waste/garbage disposal is (58.3%) in the piled garbage, cleaning habits of respondents in a home environment that is (66.7%) 1 times a day and clean the floor of the house is the state (58.3%) cement flooring. It is expected that the elderly still maintaining knowledge of respiratory diseases, keeping the environment both home/work and always went to health care to get treatment.